Towards Symmetric Thioamides: Microwave-Aided Synthesis of Terephthalic Acid Derivatives - Andrzej Bak; Violetta Kozik; Aleksandra Swietlicka; Wojciech Baran; Adam Smolinski; Andrzej Zięba (MDPI AG, 2023)
The multistep synthesis of novel bis-terephthalthioamides based on methyl esters of amino acids (AAs) was proposed using conventional heating and microwave-assisted approaches. In fact, the comparative case study on the thionation of new symmetrical diamides with Lawesson's reagent (LR) was performed. The microwave-accelerated small-scale methodology was successfully employed on the whole pathway from substrates (Gly, Ala, Val, Tyr, Ser) to products (symmetrical dithioamides of terephthalic acid), resulting in significantly reduced reaction time, energy requirements, and slightly increased reaction yields when compared to conventional heating. Moreover, the intermolecular similarity of novel terephthalic acid derivatives was estimated in the multidimensional space (mDS) of the structure/property-related in silico descriptors using principal component analysis (PCA) and hierarchical clustering analysis (HCA). The distance-oriented structure/property distribution was also correlated with the experimental lipophilic data.